Textbook on administrative law - Leyland, Peter (Oxford University Press, 2009)
The sixth edition of Textbook on Administrative Law has been substantially rewritten to provide a concise and topical account of this fast-moving area of law. The guiding theme for this acclaimed textbook is how accountability is achieved through a 'grievance chain' comprising Parliament, informal methods of dispute resolution, ombudsmen, tribunals, and particularly, by the courts through judicial review. This edition remains as accessible as ever, fully exploring the core areas of the subject and setting them in a contextual framework. In addition to wide-spread recognition as an invaluable core text for LLB and CPE students, Leyland and Anthony is a stimulating introduction to administrative law for postgraduates and for non-law undergraduates with an interest in the field